2005
DOI: 10.5713/ajas.2005.1048
|View full text |Cite
|
Sign up to set email alerts
|

Acidifier as an Alternative Material to Antibiotics in Animal Feed

Abstract: Dietary acidifiers appear to be a possible alternative to feed antibiotics in order to improve performance of weaning pigs. It is generally known that dietary acidifiers lower gastric pH, resulting in increased activity of proteolytic enzymes, improved protein digestibility and inhibiting the proliferation of pathogenic bacteria in GI tract. It is also hypothesized that acidifiers could be related to reduction of gastric emptying rate, energy source in intestine, chelation of minerals, stimulation of digestive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 56 publications
(85 reference statements)
0
76
0
3
Order By: Relevance
“…Capacity to decrease pH in the feed and GI tract by the organic acid likely dependent on the pH conditions of the GIT and pKa values of the organic acid used (Kim et al, 2005). The pH reduction in GI tract is more pronounced in the upper part.…”
Section: Organic Acidsmentioning
confidence: 99%
“…Capacity to decrease pH in the feed and GI tract by the organic acid likely dependent on the pH conditions of the GIT and pKa values of the organic acid used (Kim et al, 2005). The pH reduction in GI tract is more pronounced in the upper part.…”
Section: Organic Acidsmentioning
confidence: 99%
“…It was demonstrated that vitamin C alleviates the effects of stress in the body (5,12,45) and may indirectly contribute to the improvement of many indicators of sow's reproductive performance. It is likely that vitamin C also acts similarly to other organic acidifiers that along with lowering the pH, increase the activity of proteolytic enzymes and inhibit the growth of pathogenic gastrointestinal flora, thereby improving digestion, absorption, and retention of nutrients (19), and in consequence affect the improvement of piglets rearing results (11).…”
Section: Resultsmentioning
confidence: 99%
“…Organic acids (OA) have been used as the first alternative to in-feed antibiotics by many feed companies, especially in diets for piglets (Kim et al, 2005;Mroz, 2005). Meta-analysis confirms that OA improve performance of weaned piglets, but the significance and magnitude of the effect appears to depend on the type and level of the OA used, as well as differences in feed composition and buffering (Partanen and Mroz, 1999;Partanen, 2001).…”
Section: Introductionmentioning
confidence: 99%